2014
DOI: 10.1016/j.bone.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

MKP-1 signaling events are required for early osteoclastogenesis in lineage defined progenitor populations by disrupting RANKL-induced NFATc1 nuclear translocation

Abstract: Cytokine-directed osteoclastogenesis is initiated in response to macrophage colony stimulating factor (M-CSF) and receptor activator of NF-κB ligand (RANKL), to drive formation of osteoclasts (OC), large bone resorptive cells of hematopoietic origin. RANKL-induced signaling activates the MAPK pathways, which initiates nuclear translocation of the master regulator of osteoclast formation, transcription factor NFATc1. Proper control over these signaling events is essential to normal OC formation response to stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 38 publications
0
27
1
Order By: Relevance
“…Previously work from our lab has shown that MKP-1 is necessary for proper OC formation in response to RANKL by regulating NFATc1 nuclear translocation and downstream OC gene expression [6]. In contrast, the current study found that NFATc1 gene expression was not dysregulated between genotypes following LPS stimulation (data not shown).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Previously work from our lab has shown that MKP-1 is necessary for proper OC formation in response to RANKL by regulating NFATc1 nuclear translocation and downstream OC gene expression [6]. In contrast, the current study found that NFATc1 gene expression was not dysregulated between genotypes following LPS stimulation (data not shown).…”
Section: Discussioncontrasting
confidence: 86%
“…Based on this concept, high levels of CD11b are considered macrophage-committed monocytes, while CD11b lo cells have the highest osteoclast potential [4] [5]. Consistent with these observations, we and others have shown that BM dOCP enrichment of the CD11b lo population yields large, highly functional OC in response to physiological stimuli, macrophage colony stimulating factor (M-CSF) and receptor activator of NF-κB ligand (RANKL) [6]. …”
Section: Introductionmentioning
confidence: 67%
“…To determine the MKP‐1 agonistic effect of ARN on mouse macrophages, RAW264.7 cells were plated onto 6‐well dishes at 1 × 10 6 cells per well, allowed to adhere overnight and treated with free ARN diluted in DSMO (100, 50, 10, or 1 µM) or ARN encapsulated in NP at 10, 1, or 0.1 µM final concentration. RNA was harvested after 4, 8, 24, 48, or 72hours exposure to treatments using Trizol as previously described . Purified mRNA was measured from each sample for yield and purity .…”
Section: Methodsmentioning
confidence: 99%
“…Using preclinical models of periodontal disease progression, we have established through loss‐ or gain‐of‐function studies that MKP‐1 signaling impacts alveolar bone loss in preclinical models of periodontal diseases . ‒ In addition, we have published that MKP‐1 signaling is required for RANKL‐induced osteoclastogenesis while MKP‐1 signaling is a negative regulator of lipopolysaccharide (LPS)‐induced osteoclastogenesis . While MKP‐1 agonists have not been developed into FDA‐approved therapeutics, there are a few agents that are FDA‐approved that harbor MKP‐1 agonist properties .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the remaining red blood cells were lysed in lysis buffer and enumerated with trypan blue dead cell exclusion dye. Cells were stained with commercially available antibodies, including anti-CD11b Ϫ -allophycocyanin (APC) (clone M1/70, rat IgG2b; Miltenyi Biotec Inc., San Diego, CA, USA), anti-CD11b Ϫ -fluorescein isothiocyanate (clone M1/70, rat IgG2b; Miltenyi Biotec Inc., San Diego, CA, USA), anti-mouse CCR1-APC (clone 643854, rat IgG2b; R&D Systems, Minneapolis, MN, USA), anti-mouse CD195/CCR5-peridinin chlorophyll protein-Alexa Fluor 710 (clone 7A4, Armenian hamster IgG; eBioscience, Inc., San Diego, CA, USA), and anti-mouse CCR2-APC (clone 475301, rat IgG2b; R&D Systems, Minneapolis, MN, USA) following previously described methods (36). Prior to analysis, debris was gated out using forward scatter and side scatter plots, and dead cells were excluded using propidium iodide staining.…”
Section: Methodsmentioning
confidence: 99%